Rapid Multiplication of Carallia brachiata (Lour) Merr. By Terminal Branch Cuttings - Kumar, R. Vijaya; Murthy, A. R. S.; Srivasuki, K. P. (Indian Forester, 1993)
Root initiation in Carallia brachiata, (Kierpa) terminal branch cuttings is studied by treating with Indole Butyric Acid (IBA) (2000 ppm), as quick dip and placing them under mist. Good results were obtained with respect to number of roots and time taken for root initiation at 2000 ppm concentration of IBA. This technique is useful in rapid propagation of the species which otherwise is a problem due to poor germination of the seed. Moreover greater genetic uniformity can be achieved in planting stocks by adapting this technique.